Second International Conference on Systems (ICONS'07) 2007
DOI: 10.1109/icons.2007.7
|View full text |Cite
|
Sign up to set email alerts
|

A system to aid blind people in the mobility: A usability test and its results

Abstract: Blind people need to become as independent as possible in their daily life in order to guarantee a fully social inclusion. Mobility means the possibility of freely moving, without support of any accompanying person, at home, in public and private buildings, and in open spaces, as the streets of the town. Mobile and wireless technologies, and in particular the ones used to locate persons or objects, can be used to realize navigation systems in an intelligent environment. Such systems open new opportunities to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 10 publications
0
31
0
Order By: Relevance
“…Soundbased VEs have been investigated and developed for blind persons (D'Atri et al, 2007;Gonzalez-Mora, 2003;Kurniawan, Sporka, Nemec, & Slavik, 2004;Sán-chez, Noriega, & Farías, 2008;Seki & Sato, 2011); however, this research showed that successful exploration using only sound requires a very high level of attention. Haptics, which refers to sensing and manipulation through touch, is another modality for interacting with a VE that can provide the user with tactile, kinesthetic, and reaction force information about the environment, as well as a means of controlling events in the VE.…”
Section: Introductionmentioning
confidence: 99%
“…Soundbased VEs have been investigated and developed for blind persons (D'Atri et al, 2007;Gonzalez-Mora, 2003;Kurniawan, Sporka, Nemec, & Slavik, 2004;Sán-chez, Noriega, & Farías, 2008;Seki & Sato, 2011); however, this research showed that successful exploration using only sound requires a very high level of attention. Haptics, which refers to sensing and manipulation through touch, is another modality for interacting with a VE that can provide the user with tactile, kinesthetic, and reaction force information about the environment, as well as a means of controlling events in the VE.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years some research teams [4][5][6] have developed navigation systems based on this technology. In the case of outdoor environments, some hybrid systems have been proposed that use GPS as the main information source and use RFID for correction and minimization of the location error.…”
Section: Related Workmentioning
confidence: 99%
“…The Sesamonet system is composed by an electronic path made of low-frequency RFID transponders (1), a custom made electronic stick (2) and a PDA/Smartphone (3) eventually equipped with a Bluetooth earphone (4). Each component is shown in Fig.…”
Section: A Components Analysismentioning
confidence: 99%
“…With the aim of giving the possibility of an independent and safe mobility to blind persons, an assistive system based on RFID technology named Sesamonet has been designed, developed and patented at the Joint Research Centre (JRC) of the European Commission [3,4]. Since the first patent registration in 2006 [5] the system has continuously been improved: in the following sections of the article a general overview of the system history, components and functioning is presented.…”
Section: Introductionmentioning
confidence: 99%